Performance of Internet of Things (IoT) Potential Applications in Education - Ane, Tanjea; Billah, Masum; Nepa, Tabatshum (Bangladesh Journal of Multidisciplinary Scientific Research, 2020)
Internet of Things (IoT) very fast growing interaction that has connected real and virtual objects anytime, anywhere though network. A variety of various connected objects influence the applications of education process which is like a new change with research opportunities and possibilities. In education ecosystem IoT emerges as rapidly dynamic technology for the improvement of traditional education system. This paper consists of five parts: firstly an overview of IoT use, secondly IoT application in education system, thirdly recent survey IoT work then discusses IoT impacts in the higher education and concludes the paper.